Implicit and explicit racial prejudice among medical professionals: updated estimates from a population-based studyResearch in context - Tiffany L. Green; Hoa Vu; Laura E.T. Swan; Dian Luo; Ellen Hickman; Marie Plaisime; Nao Hagiwara (The Lancet Regional Health. Americas, 2023)
Summary: Background: Prior research provides evidence of implicit and explicit anti-Black prejudice among US physicians. However, we know little about whether racialized prejudice varies among physicians and non-physician healthcare workers relative to the general population. Methods: Using ordinary least squares models and data from Harvard's Project Implicit (2007–2019), we assessed the associations between self-reported occupational status (physician, non-physician healthcare worker) and implicit (N = 1,500,268) and explicit prejudice (N = 1,429,677) toward Black, Arab-Muslim, Asian, and Native American populations, net of demographic characteristics. We used STATA 17 for all statistical analyses. Findings: Physicians and non-physician healthcare workers exhibited more implicit and explicit anti-Black and anti-Arab-Muslim prejudice than the general population. After controlling for demographics, these differences became non-significant for physicians but remained for non-physician healthcare workers (β = 0.027 and 0.030, p < 0.01). Demographic controls largely explained anti-Asian prejudice among both groups, and physicians and non-physician healthcare workers exhibited comparatively lower (β = −0.124, p < 0.01) and similar levels of anti-Native implicit prejudice, respectively. Finally, white non-physician healthcare workers exhibited the highest levels of anti-Black prejudice. Interpretation: Demographic characteristics explained racialized prejudice among physicians, but not fully among non-physician healthcare workers. More research is needed to understand the causes and consequences of elevated levels of prejudice among non-physician healthcare workers. By acknowledging implicit and explicit prejudice as important reflections of systemic racism, this study highlights the need to understand the role of healthcare providers and systems in generating health disparities. Funding: UW-Madison Centennial Scholars Program, Society of Family Planning Research Fund, UW Center for Demography and Ecology, the County Health Rankings and Roadmaps Program and the National Institutes of Health (NIH).